The The Application Of The Geneva Convention, 1949, In Malaysia - Ibrahim, Ahmad (Journal of Malaysian and Comparative Law, 2019)
Although Islam is the religion of the Federaion, the law that is applicable and followed in Malaysia (apart from certain family and religious matters affecting the Muslim) is not the Islamic Law. In the field of humanitarian law, the law is contained in legislation based on similar legislation in the United Kingdom.